Untapping the potential of Indigenous water jurisdiction: perspectives from Whanganui and Aotearoa New Zealand - Elizabeth Macpherson; Hayden Turoa (Humanities & Social Sciences Communications)
Abstract Indigenous peoples have maintained sustainable, longstanding relationships with water and have valuable knowledge to contribute to water management. Still, legal and policy frameworks routinely include only tokenistic acknowledgements of Indigenous water ‘values’, while ongoing injustices related to the allocation and governance of water resources remain unresolved. Those concerned about the recognition of Indigenous water rights and relationships often point to the case of Aotearoa New Zealand, and specifically the Treaty of Waitangi settlement legislation recognising the Whanganui River as a ‘legal person’, as a replicable model for improved water governance and Indigenous water rights. In this article we use a sociolegal method to draw out globally relevant lessons from the groundbreaking Whanganui River model about the potential for Western or settler-state law to support and uphold Indigenous rights and relationships in water. Our analysis confirms that enabling Indigenous water jurisdiction could hold the key to more sustainable and equitable futures, but it requires a long-term commitment from states and local communities to relationship brokering, power sharing, and trust building with Indigenous peoples.